How Do Life Partners and Their Occupational Choice Affect the Path of Transition to Entrepreneurship? A Comparison Between Direct and Indirect Entry into Entrepreneurship - Cemre Demir; Meike Stephan; Arndt Werner (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
Although hybrid entrepreneurship constitutes a significant share of entrepreneurial activity, research on this topic is still in its infancy. Moreover, in general entrepreneurship research only few studies have investigated intra-couple influences on the decision to be and to become self-employed. Therefore, in the study at hand, we use panel data from the German Socio-Economic Panel (GSOEP) to analyse whether life partners and their occupational choice relate to wage workers' propensity to enter full-time entrepreneurship either directly or indirectly via hybrid entrepreneurship. Drawing on social capital theory, this study also tests whether the results are different for men and women. Although hypothesised, we find no empirical evidence for the relevance of life partners and their occupations on direct transition to full-time entrepreneurship. For women, however, our findings do suggest that having a self-employed life partner significantly increases their propensity to enter entrepreneurship indirectly, that is, via hybrid entrepreneurship.
Keywords: L26; D81; J16; 330; Hybrid Entrepreneurship; Social Capital; Life Partner; Occupation; Gender-Related Differences